GEREJA RAMAH DISABILITAS: MEWUJUDKAN INKLUSI SOSIAL BERBASIS NILAI TEOLOGIS DAN IMPLIKASINYA BAGI PENDIDIKAN INKLUSIF - Yendri Aldewi; Fandrio Logo, Mariana Bulan, Yanti Djo, Mince Metta, Oni Tualaka, Zerly Nubatonis, Priskal Lopo, Nof (CV. ADIBA ASIHA AMIRA, 2026)
This article examines the concept of a disability-friendly church through theological and sociological perspectives and its implications for inclusive education. Using a qualitative research method with a library research approach, this study reviews various academic sources, policy documents, and relevant biblical texts. The findings indicate that biblical theology, particularly the concept of imago Dei and Pauline ecclesiology, provides a strong theological foundation for disability inclusion within church communities. A disability-friendly church demands not only physical accessibility but also a transformation of theological, pastoral, and structural-organizational paradigms. The inclusive church model formulated encompasses four main dimensions: theological-doctrinal, liturgical-pastoral, structural-accessibility, and educational-community. Implications for inclusive education include the development of adaptive Christian Religious Education (CRE) curricula, the formation of teachers and companions who are sensitive to the needs of persons with disabilities, and the strengthening of partnerships between the church, families, and Christian schools. This article asserts that the church holds great transformative potential to become a laboratory of social inclusion that can inspire broader educational system reform.